Efeito materno para a característica de tolerância à termoinibição em sementes de alface (Lactuca sativa) - Cavasin, Pedro Yuri (2019)
Lettuce (Lactuca sativa) is the most important leafy vegetable in the world and the most commercialized in Brazil. The low germination due to high temperatures (> 25ºC) is one of the most serious problem in the lettuce seeds production in the country. In Brazil the tropical climate is predominant which provides a favorable environment for the germination inactivation by thermodormancy and or thermoinhibition. Therefore, it is important the development of cultivars whose germination occurs satisfactorily at higher temperatures, providing improvements in production and greater seedlings stand uniformity. The Everglades cultivar presents tolerance to the thermoinhibition and is a reference in studies on lettuce germination at high temperatures. Seeds may have traits with maternal origin and the existence of this can be tested by reciprocal crosses. Many studies report that the endosperm is one of the factors of resistance to high temperatures germination, which is inherited from the the female parent. Thus, the study of genetic control is necessary to confirm the existence of a maternal effect on the tolerance to thermoinhibition in lettuce seeds as well as to define the generation to start the selection, and find possible enzyme markers.